Advances in Graphene-Based Electrode for Triboelectric Nanogenerator - Bin Xie; Yuanhui Guo; Yun Chen; Hao Zhang; Jiawei Xiao; Maoxiang Hou; Huilong Liu; Li Ma; Xin Chen; Chingping Wong (Nano-Micro Letters)
Highlights Comprehensively reviewed the progress in research on graphene electrode-based triboelectric nanogenerators (TENGs) from two dimensions, including precision processing methods of graphene electrodes and applications of TENGs. Discussed the various applications of graphene electrode-based TENGs in different scenarios, as well as the ways in which graphene electrodes enhance the performance of TENGs. Offered a prospective discussion on the future development of graphene electrode-based TENGs, with the aim of promoting continuous advancements in this field.